Toward Universal Health Coverage and Equity in Latin America and the Caribbean : Evidence from Selected Countries - Dmytraczenko, Tania; Almeida, Gisele (Washington, DC: World Bank, 2015)
This volume reviews progress in reducing inequalities in health outcomes, service utilization, and financial protection, and assesses the common trends emerging from these reforms.